2016
DOI: 10.1016/j.jim.2016.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Differential scanning fluorimetry based assessments of the thermal and kinetic stability of peptide–MHC complexes

Abstract: Measurements of thermal stability by circular dichroism (CD) spectroscopy have been widely used to assess the binding of peptides to MHC proteins, particularly within the structural immunology community. Although thermal stability assays offer advantages over other approaches such as IC50 measurements, CD-based stability measurements are hindered by large sample requirements and low throughput. Here we demonstrate that an alternative approach based on differential scanning fluorimetry (DSF) yields results comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
66
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(73 citation statements)
references
References 57 publications
(74 reference statements)
7
66
0
Order By: Relevance
“…Replacement of the p1 Lys with alanine did not weaken binding of the peptide to A2, as the A2 complexes with both the native NS3 epitope and the K1A variant had identical melting temperatures (T m values) of 64°C when measured by differential scanning fluorimetry (DSF) (Fig. 1D), reflective of high-affinity peptide binding (24).…”
Section: Resultsmentioning
confidence: 97%
“…Replacement of the p1 Lys with alanine did not weaken binding of the peptide to A2, as the A2 complexes with both the native NS3 epitope and the K1A variant had identical melting temperatures (T m values) of 64°C when measured by differential scanning fluorimetry (DSF) (Fig. 1D), reflective of high-affinity peptide binding (24).…”
Section: Resultsmentioning
confidence: 97%
“…While both 12mers formed complexes with B08 that were sufficiently stable to allow characterization (Supporting Figure 3), biophysical analysis suggested that the complexes are quite distinct in terms of thermodynamic and kinetic stability ( Figure 5A and Supporting Figure 6, Supporting Tables 1,2). Using the Differential Scanning Fluorimetry Assay (DSF) (41), the B08/LL12 complex displayed a Tm value of 57.7±0.4 °C. In contrast, the B08/AI12 complex, was markedly less stable with Tm value of 47.8±2.3 °C.…”
Section: Characterization Of Thermodynamic and Kinetic Stability Of Bmentioning
confidence: 99%
“…We utilized well-characterized epitopes: the p29 peptide (YPNVNIHNF) for H2-L d (41), the HIV gp120 P18-I10 peptide (RGPGRAFVTI) for H2-D d (42), the neuroblastoma related NRAS Q61K peptide (ILDTAGKEEY) for HLA-A*01:01 (43), and the HTLV-1 TAX peptide (LLFGYPVYV) for HLA-A*02:01 (44). Using a differential scanning fluorimetry assay (45), we further confirmed that all purified samples displayed thermal stabilities that were characteristic of properly conformed, peptide-bound molecular species with T m values ranging from 51 to 63 °C (Table S1). Using a SEC assay, we observed formation of pMHC-I/TAPBPR complexes for both mouse pMHC-I (P18-I10/H2-D d /hβ2m and NIH/H2-L d /hβ2m), but neither of the human pMHC-I (NRAS Q61K /HLA-A*01:01/hβ2m and TAX/HLA-A*02:01/hβ2m) ( Fig.…”
Section: Tapbpr Recognizes Folded Pmhc-i Using a Conserved Binding Momentioning
confidence: 99%